Lingkungan Keluarga Terhadap Kebiasaan Membaca Siswa Madrasah Ibtidaiyah - Patimah; Trimulyo, Joko (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
Students' perusing propensities are one of the competencies that must be aced by understudies, particularly within the 21st century it must be created towards proficiency aptitudes. This consider points to decide the impact of the family environment on the perusing propensities of MI understudies in Situ Udik Town, Cibungbulang Area, Bogor Rule. This thinks about uses a quantitative approach employing a basic straight relapse strategy. The populace in this think about was lesson V in one institution with a add up to of 27 tests. The technique used in information collection is an instrument within the shape of a articulation survey for the family environment and perusing propensities totaling 25 articulations each. The information collected will be analyzed utilizing basic straight relapse, the comes about gotten are that there's no critical impact between the family environment on perusing propensities since the importance esteem gotten is 0.206> 0.05. So the suggestion in this think about is that the inside components of understudies must be advance made strides since inner variables impact more than outside components in terms of perusing propensities.